The hour of revenge: Holocaust survivors and their search for revenge and retribution - Person, Katarzyna (University of Toronto Press, 2025)
"The book shows how the notion of attempting to carry out both retribution and physical revenge was a key element of the emotional landscape of the immediate post-war and included also Holocaust survivors, who on equal part became part of the post-conflict world. While there is now a considerable amount of work showing the disintegration and extra-legal purges in post-war Europe in the immediate aftermath of liberation, individual Polish Jews were usually written out of this story. They were often considered physically and emotionally incapable of getting revenge and retribution. The aim of my book is to tell the specific story of Polish Jews while filling a gap in research on post-conflict retribution and functioning of post-conflict communities. As Polish Jews left Poland and settled abroad, the book crosses the traditional historiographical post-war divide between “West” and “East”, showing how people moved between the two zones just before the Iron Curtain came down, how they dealt with their memories and how they would go on to build emotional communities, defined by shared memories. This book contributes both to writing an integrative, multi-ethnic history of post-war Poland and to the global history of rebuilding of a shattered society post-conflict."--